Surface oxidation and thermoelectric properties of indium-doped tin telluride nanowires. Issue 35 (23rd August 2017) - Li, Zhen; Xu, Enzhi; Losovyj, Yaroslav; Li, Nan; Chen, Aiping; Swartzentruber, Brian; Sinitsyn, Nikolai; Yoo, Jinkyoung; Jia, Quanxi; Zhang, Shixiong
Abstract : The In-doped SnTe nanowire surface is composed of In2 O3, SnO2, Te and TeO2 which can be readily removed by argon ion sputtering. Abstract : The recent discovery of excellent thermoelectric properties and topological surface states in SnTe-based compounds has attracted extensive attention in various research areas. Indium doped SnTe is of particular interest because, depending on the doping level, it can either generate resonant states in the bulk valence band leading to enhanced thermoelectric properties, or induce superconductivity that coexists with topological states. Here we report on the vapor deposition of In-doped SnTe nanowires and the study of their surface oxidation and thermoelectric properties. The nanowire growth is assisted by Au catalysts, and their morphologies vary as a function of substrate position and temperature. Transmission electron microscopy characterization reveals the formation of an amorphous surface in single crystalline nanowires. X-ray photoelectron spectroscopy studies suggest that the nanowire surface is composed of In2 O3, SnO2, Te and TeO2 which can be readily removed by argon ion sputtering. Exposure of the cleaned nanowires to atmosphere leads to rapid oxidation of the surface within only one minute. Characterization of electrical conductivity σ, thermopower S, and thermal conductivity κ was performed on the same In-doped nanowire which shows suppressed σ and κ but enhanced S yielding an improved thermoelectric figure of merit ZT compared to the undoped SnTe.